2012
DOI: 10.3233/jbr-2012-029
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bioactive compounds of strawberry fruit from Europe affected by genotype and latitude

Abstract: The effect of four different growing locations from Stjørdal, Norway (63 • 36 N) to Conthey, Switzerland (46 • 12 N) on the composition of bioactives in strawberry (Fragaria x ananassa Duch.) of three genotypes (cvs Clery, Elsanta and Korona) was evaluated. Principal component analysis (PCA) was used to characterize differences in bioactives between genotypes within a location. Despite harvest period and year-to-year effects, a clear clustering related to the effects of the cultivars was shown. Furthermore, PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
36
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 43 publications
12
36
1
Order By: Relevance
“…Korona and Clery) was negatively correlated to daily maximum temperature one or two weeks prior to harvest, respectively ( Table 8). The redder fruit surface in this study at lower latitudes are in agreement with the findings of Josuttis et al [16] who found in their study an increase of total anthocyanin in strawberry fruit from north to south. This increase of total anthocyanins was mainly caused by the increased content of pelargonidin 3-glucoside, which is one of the major anthocyanins giving strawberry fruit their red colour.…”
Section: Outer Fruit Quality: L* Chroma and Huesupporting
confidence: 93%
See 1 more Smart Citation
“…Korona and Clery) was negatively correlated to daily maximum temperature one or two weeks prior to harvest, respectively ( Table 8). The redder fruit surface in this study at lower latitudes are in agreement with the findings of Josuttis et al [16] who found in their study an increase of total anthocyanin in strawberry fruit from north to south. This increase of total anthocyanins was mainly caused by the increased content of pelargonidin 3-glucoside, which is one of the major anthocyanins giving strawberry fruit their red colour.…”
Section: Outer Fruit Quality: L* Chroma and Huesupporting
confidence: 93%
“…Fruit sampling and sample preparation are described in detail by Josuttis et al [16]. Briefly, at all sites, samples of 500 g of healthy fruit per replicate were collected twice in the middle of the harvest period.…”
Section: Fruit Quality Characteristics: Dry Matter Soluble Solids Tmentioning
confidence: 99%
“…The studies conducted on 27 cultivars from Norway [9], 20 from Spain [10,11], 3 from Turkey [12], and 4 from Macedonia [13] revealed large differences in phenolics composition and antioxidant activity of strawberry fruits between cultivars. A recently published paper indicated that genotype was a major determining factor of bioactive components [14]. Currently the efforts of breeding programs are focused on developing new cultivars with enhanced flavour and preferably also improved levels of health-beneficial compounds [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…While the number of studies targeted at characterising enzymatic activity of these enzymes in soft‐fruit in response to different photoperiods is extremely limited, it is reasonable to surmise that photoperiod could be having an effect on sugar/organic acid ratio by modulation of the activity of such enzymes. However, a number of studies aimed at characterising the biochemical composition of strawberry to different latitudes have observed generally that plants grown at northern latitudes in Europe have significantly higher soluble sugar content (Davik et al ., ; Josuttis et al ., ). Such findings suggest the existence of a complex interplay of responses to a range of environmental factors, such as temperature and photoperiod, in the balance between sugar and organic acid content.…”
Section: Discussionmentioning
confidence: 97%
“…The fact that the daily light energy is also particularly high during the long summer days at high latitude further supports this likelihood. However, since such latitude‐related effects are confounded by a number of co‐varying environmental factors, it has proved difficult to sort out the causal relations under natural conditions (Jaakola & Hohtola, ; Josuttis et al ., ). In order to reduce these complications as much as possible, an experimental approach similar to the present one should be attempted, using pot‐grown long cane plants with high yield potential, and delay their distribution to a range of latitudinal growing sites until the plants have started flowering.…”
Section: Discussionmentioning
confidence: 97%